Orientation and ambiguity – On a decisive hermeneutical dimension in Dirkie Smit’s theological thinking - Fouché, Leon (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
This essay explores Dirkie Smit’s theological thinking from a hermeneutical perspective. Smit’s linking up with Karl Barth’s view on confessing, as can be seen in the Accompanying Letter of the Belhar Confession, is taken as illustration. After a historical perspective on the philosophical hermeneutics of Hans-Georg Gadamer with its central concepts of historicality, contextuality, orientation and dialogue, it is demonstrated how these concepts also play a significant role in Smit’s way of doing theology. Barth’s three aspects of Reformed confessions (historical context, the one message and the one church) are associated with three Gadamer’s concepts of historicality, orientation and contextuality. While Gadamer’s philosophical hermeneutics move from application (contextuality) to practical philosophy, Smit’s theology moves from contextuality to public theology. Confessing the old Christian creed that Jesus is Lord in the public sphere as the church’s decisive orientation contains the risk of ambiguity within an ongoing dialogue. The argument of the article is that the core of Smit’s theological thinking can be understood as orientation and ambiguity amidst the dialectic of historicality and contextuality.